Occurrence, antimicrobial susceptibility patterns and genotypic relatedness of Salmonella spp. isolates from captive wildlife, their caretakers, feed and water in India. Issue 12 (14th June 2018) - Milton, Arockiasamy Arun Prince; Agarwal, Rajesh Kumar; Priya, Govindarajan Bhuvana; Athira, Cheruplackal Karunakaran; Saminathan, Mani; Reddy, Avinash; Aravind, Manivasagam; Kumar, Ashok
Abstract: Occurrence of Salmonella spp. in captive wild animal species in India is largely unknown. The purpose of this study was to determine the occurrence of different Salmonella serotypes, antimicrobial resistance patterns and genotypic relatedness of recovered isolates. A total of 370 samples including faecal ( n = 314), feed and water ( n = 26) and caretakers stool swabs ( n = 30) were collected from 40 different wild animal species in captivity, their caretakers, feed and water in four zoological gardens and wildlife enclosures in India. Salmonellae were isolated using conventional culture methods and tested for antimicrobial susceptibility with the Kirby–Bauer disc diffusion method. Salmonella isolates were serotyped and genotyping was performed using enterobacterial repetitive intergenic consensus (ERIC) PCR and 16S rRNA sequencing. Animal faecal samples were also subjected to direct PCR assay. Salmonella was detected in 10 of 314 (3.1%) faecal samples by isolation and 18 of 314 (5.7%) samples by direct PCR assay; one of 26 (3.8%) feed and water samples and five of 30 (16.7%) caretakers stool swabs by isolation. Salmonella was more commonly isolated in faecal samples from golden pheasants (25%; 2/8) and leopard (10%; 2/20). Salmonella enterica serotypes of known public health significance including S . Typhimurium (37.5%; 6/14), S . Kentucky (28.5%; 4/14) and S . Enteritidis (14.3%; 2/14) were identified. While the majority of the Salmonella isolates were pan-susceptible to the commonly used antibiotics. Seven (43.7%; 7/16) of the isolates were resistant to at least one antibiotic and one isolate each among them exhibited penta and tetra multidrug-resistant types. Three S . Kentucky serotype were identified in a same golden pheasants cage, two from the birds and one from the feed. This serotype was also isolated from its caretaker. Similarly, one isolate each of S . Typhimurium were recovered from ostrich and its caretaker. These isolates were found to be clonally related suggesting that wildlife may serve as reservoir for infections to humans and vice versa. These results emphasise the transmission of Salmonella among hosts via environmental contamination of feces to workers, visitors and other wildlife.